Education and construction schools of social justice. lnitiatives for a cartography from Latin America: Iniciativas para una cartografía desde América Latina (Praxis Educativa, 2023)
The article presents the progress of a cartography of educational and pedagogical initiatives in Latin Americathat contribute to the construction of social justice in educational scenarios. The research that originates itdeveloped diálogos de saberes with educators who build just emancipatory praxis and who are committedto building other educational realities in which decolonized, depatriarchalized and decapitalized individualand collective subjectivities are formed in their ways ofthinking and acting. The guiding thread ofthesereflections is the stubborn hope that another world and, therefore, another education is possible, bydenaturalizing injustices, breaking structurally installed binarisms and inequalities and, from the subjectivepower, weaving in the micropolitical daily life of the classroom and the institutions, just praxis.
Keywords: social justice, decolonization, depatriarchalization, decapitalization, educational cartography.